Shodaqoh Sampah: Perempuan Dalam Pengelolaan Sampah di Dusun Sukunan, Desa Banyuraden, Gamping, Daerah Istimewa Yogyakarta - Muryanti Muryanti (Jurnal Empirika, 2016)
The Shodaqoh of rubbish is collective behavior are changed rubbish become a good things from residue. Women have been dominant activities, in the classifications of rubbish in the household, make product handy craft, socialization, supply accommodation to guest in training of rubbish management. This research use qualitative method. Explore data trough in-depth interview and observation as primer data. Ecofeminism perspective believe that all of activities women must be done by awareness, not only by social construction that women are feminine and care. All of activities women in Dusun Sukunan are not suitable with Ecofeminism perspective. They done because of nature character. So the awareness process must be done.Â Â